Serum protein coating enhances the antisepsis efficacy of silver nanoparticles against multidrug-resistant Escherichia coli infections in mice - Du, Huamao; Wang, Xiaoling; Zhang, Hongying; Chen, Heming; Deng, Xiaoyu; He, Yujing; Tang, Huaze; Deng, Fuchang; Ren, Zhihong (Frontiers in Microbiology, 2023)
Abstract: Antimicrobial resistance is a severe threat to global public health and social development. In this study, the potency of silver nanoparticles (AgNPs) in the treatment of multi-drug resistant bacterial infections was comprehensively determined. The sphere AgNPs ecofriendly synthesized with rutin at room temperature. Both polyvinyl pyrrolidone (PVP) and mice serum (MS) stabilized AgNPs have available biocompatibility at 20 μg/mL and similar distribution in mice. However, only MS-AgNPs significantly protect mice against sepsis caused by multidrug resistant Escherichia coli (E. coli) CQ10 strain (p=0.039). The data showed that MS-AgNPs facilitated to eliminate E. coli in blood and spleen, and the mice experienced slight inflammatory response since interleukin-6 、tumor necrosis factor-α、chemokine KC and C-reactive protein significantly lower than that of control group. The results suggest that plasma protein corona strengthen the antibacterial effect of AgNPs in vivo, and may be a potential strategy for antimicrobial resistance problem.